Electromechanical Properties of Carbon Nanotube Infused Polyacrylamide Hydrogel. Issue 2 (7th November 2014) - Jackson, Nathan; Sheehan, Aisling; Hasan, Maksudul; Stam, Frank; Razeeb, Kafil M.
ABSTRACT Typically, electroresponsive hydrogels have either a high electrical conductivity with little swelling or large swelling with low conductivity. This paper investigates a method of maintaining high swelling capabilities and increasing electrical conductivity by infusing multiwalled carbon nanotubes (MWCNTs) into a hydrolyzed polyacrylamide hydrogel. Various concentrations of MWCNT and Nafion solutions infused into the hydrogel were investigated. Optical microscopy analysis showed aggregates of carbon nanotube bundles at the macroscale, whereas electron microscopy revealed homogeneous dispersion of carbon nanotube in the polymer matrix at the microscale. Electrical conductivity measurements demonstrated an increase from 0.02 to 0.11 mS cm–1 with infused MWCNT. The MWCNT‐infused hydrogels demonstrated a 400% increase in deswelling capabilities during an applied electrical stimulus compared to a noninfused hydrogel. In conclusion, infusing the MWCNT into the hydrogel increased its electrical conductivity, which allows the hydrogel to deswell more rapidly with an applied electrical bias without compromising its mechanical or swelling properties.